1995
DOI: 10.1007/bf01213271
|View full text |Cite
|
Sign up to set email alerts
|

Right hepatic lobe agenesis associated with bile duct carcinoma

Abstract: A patient with obstructive jaundice was found to have bile duct carcinoma and right hepatic lobe agenesis. The diagnosis was made by computed tomography (CT), cholangiography, and angiography. Right hepatic lobe agenesis is a rare anomaly and has never been previously reported with bile duct carcinoma. CT cholangiography was critical in diagnosing the morphologic anomalies of the bile duct in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A retrohepatic gallbladder may be produced by atrophy of the right lobe [8,13,[15][16][17][18]. Brown et al reported a case with alcoholic liver cirrhosis in which CT examination performed successively during a period of 26 months showed a successive displacement of the gallbladder to the back associated with a progressive rapid atrophy of the right lobe of the liver [13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A retrohepatic gallbladder may be produced by atrophy of the right lobe [8,13,[15][16][17][18]. Brown et al reported a case with alcoholic liver cirrhosis in which CT examination performed successively during a period of 26 months showed a successive displacement of the gallbladder to the back associated with a progressive rapid atrophy of the right lobe of the liver [13].…”
Section: Discussionmentioning
confidence: 96%
“…Often the condition is the result of insufficient portal flow secondary to liver cirrhosis or bile duct carcinoma [13][14][15]. The position of the gallbladder differs with changes in hepatic morphology.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11] To our knowledge, this represents the only case in the literature of biliary injury after laparoscopic cholecystectomy in the setting of complete agenesis of the right hemiliver. It also seems to be the only description of the unusual hepatic vein anatomy in this condition.…”
Section: Discussionmentioning
confidence: 98%
“…Before the introduction of cross-sectional imaging modalities, such as ultrasonography (US), computed tomography (CT), and magnetic resonance imaging, it was discovered during laparotomy or autopsy or was detected by more invasive studies such as angiography and percutaneous cholangiography. Since the use of US and CT, several articles discussing the diagnosis of this entity by CT and US have been published [1][2][3][4][5]. The imaging modalities used included CT, US, angiography, percutaneous cholangiography, and hepatobiliary scintigraphy, with CT being the most commonly used.…”
mentioning
confidence: 99%